Peran Mata Kuliah Teknik Presentasi dan Negosiasi Terhadap Kemampuan Public Speaking Melalui Metode Role Playing pada Mahasiswa Program Studi D IV MICE Politeknik Negeri Medan - Yohana Yulianti Simbolon (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the role of the Presentation and Negotiation Techniques course in improving public speaking skills through the Role Playing Method among students of the D IV MICE Study Programme at the Medan State Polytechnic. Public speaking skills are a necessary competency in the MICE industry in order to support successful communication and the achievement of company objectives. The role playing method was chosen for classroom learning because it represents real-life situations, allowing students to play various roles according to scenarios designed and presented in class. This method also provides opportunities for students to practise persuasive communication skills, the ability to convey information effectively, and build confidence in dealing with various types of clients in the MICE industry.  This study used a qualitative descriptive method through observation, in-depth interviews, and documentation of 24 students in the MICE 5C class. The results showed that learning through the Role Playing Method contributed to an improvement in public speaking. However, it was not yet optimal because students still had difficulty applying public speaking skills consistently. This study emphasises the importance of an intensive practice-based learning approach, industry simulations, and structured feedback to continuously improve students' public speaking competence and ensure that their skills are in line with the needs of the MICE industry.